BIOLOGICAL EFFECT OF THE ENTOMOPATHOGENIC FUNGUS,Beauveria Bassiana (BALSAMO) VUILLEMIN ON THE POTATOTUBER MOTH, Phthorimaea Operculella (SELLER) - Shefik, Maan (Iraqi Journal of Science, 2024)
This study has been carried to evaluate the effect of the entomopathogenic fungiBeauveria bassiana on the various developmental stages of Phthorimaeaoperculella. Both first and second instars larvae were more susceptible than the thirdand fourth instars. The infected prepupae and pupae resulted in marked decreases inthe emergence and longevity of moths, deposited eggs and egg hatchability. Anobvious increase in the pupal duration was observed and malformed adults were alsorecorded. The latent was markedly obvious, especially in high doses of B. bassiana.